Sclerotherapy for Benign Cystic Lesions of the Head and Neck: Systematic Review of 474 Cases. (December 2021) - Talmor, Guy; Nguyen, Brandon; Mir, Ghayoour; Badash, Ido; Kaye, Rachel; Caloway, Christen
Objective: The role of sclerotherapy for vascular lesions of the head and neck is well established. However, the efficacy of sclerotherapy for benign cystic lesions of the head and neck is less clear. The objective of this review is to determine the efficacy and safety of sclerotherapy for benign cystic lesions of the head and neck. Data Sources: PubMed/MEDLINE, Cochrane Library, and Embase. Review Methods: The PRISMA guidelines (Preferred Reporting Systems for Systematic Reviews and Meta-analyses) were followed for this systematic review. Studies of patients with benign head and neck cystic masses treated primarily with sclerotherapy were included. Thirty-two studies met criteria for inclusion. Results: A total of 474 cases of sclerotherapy were reviewed. Agents comprised OK-432, ethanol, doxycycline, tetracycline, and bleomycin. Lesions in the analysis were ranula, thyroglossal duct cyst, branchial cleft cyst, benign lymphoepithelial cyst, parotid cyst, thoracic duct cyst, and unspecified lateral neck cyst. A total of 287 patients (60.5%) had a complete response; 132 (27.9%) had a partial response; and 55 (11.6%) had no response. OK-432 was the most widely utilized agent, with a higher rate of complete response than that of ethanol (62.0% vs 39.4%, P = .015). Fifty-three cases (11.2%) required further surgical management. One case of laryngeal edema was reported and managed nonoperatively. Conclusion: Sclerotherapy appears to be a safe and efficacious option for benign cystic lesions if malignancy is reliably excluded. Efficacy rates are comparable to those of sclerotherapy for vascular malformations. The rate of serious complications is low, with 1 incident of airway edema reported in the literature.